If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 17x + 5 + -5x Reorder the terms: 15 = 5 + 17x + -5x Combine like terms: 17x + -5x = 12x 15 = 5 + 12x Solving 15 = 5 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 15 + -12x = 5 + 12x + -12x Combine like terms: 12x + -12x = 0 15 + -12x = 5 + 0 15 + -12x = 5 Add '-15' to each side of the equation. 15 + -15 + -12x = 5 + -15 Combine like terms: 15 + -15 = 0 0 + -12x = 5 + -15 -12x = 5 + -15 Combine like terms: 5 + -15 = -10 -12x = -10 Divide each side by '-12'. x = 0.8333333333 Simplifying x = 0.8333333333
| 5+3c+4c= | | 14=9x+2-6 | | 1=3u-5 | | 16x^3+250=0 | | 1/2(2x-6)=4(1/4x-3/4) | | 28y+8=16 | | 6x+29=13-48 | | -7x+8+-4+-9= | | 20*log(x)=55 | | 2.00+1.50=54.5 | | -3(4v-9)+7v=4(v+6) | | 20log(x)=55 | | 2(12p+16)= | | 6=-4.1+r | | x+.06x=400 | | 268+3*g=654 | | -25.8=43v | | 268+3*g=900 | | h=15t-4.9t^2+2 | | c+4.3=-6.7 | | 5x+1=-5x-1 | | (Dy/dx)=3e^5 | | 5.6=f-64 | | 148-(56+j)=24 | | 12x-2.4.2x-1/8x.3x-4 | | 7y+-8y= | | 6.5h=39 | | 4(2x-1)=27+2(2x-5) | | 12x-2.4.2x-1/8x.3x-1 | | 73.2=6.1 | | 6x-34=100x+1 | | 6(2a-b)-15(2a-b)(2a-b)=x |